1984
DOI: 10.1017/s0001566000007261
|View full text |Cite
|
Sign up to set email alerts
|

The High Incidence of Reading Disability in Twin Boys and Its Implications for Genetic Analyses

Abstract: In 1975 the Australian Council of Educational Research (ACER) conducted a nationwide survey of literacy and numeracy in 10- to 14-year olds. A total of 297 of the 12875 children involved were twins. By age 14, only 42% of the twin boys achieved adequate standards of literacy compared with 71% of single-born boys. The deficit in twin girls was much less and twins of both sexes were only moderately behind in numeracy. A survey of 9-13-year-old twin boys in the La Trobe Twin Study (LTS) produced similar results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 16 publications
3
38
0
Order By: Relevance
“…It is well documented that twins are more likely to experience language and speech delays than singletons (2,4,7,10). Apart from prenatal and perinatal complications (12), the postnatal rearing environment is also likely to influence twins' language development, two important factors in this being the reduced opportunity for dual interaction with the mother and the competition that can exist between twins (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that twins are more likely to experience language and speech delays than singletons (2,4,7,10). Apart from prenatal and perinatal complications (12), the postnatal rearing environment is also likely to influence twins' language development, two important factors in this being the reduced opportunity for dual interaction with the mother and the competition that can exist between twins (14).…”
Section: Discussionmentioning
confidence: 99%
“…While some authors have argued that twins 'catch up'in their language development, recent research has shown that language problems can persist into adolescence. In an analysis of a large representative Australian educational survey, Hay et al (7) found twins, especially males, to have specific deficits in literacy and numeracy skills and to retain these throughout adolescence. These authors hypothesized a twin problem of impulsivity and attention that influenced performance across a broad range of academic tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Especi al l y i n the fi el d of cognitive abilities twins are generally considered to be at a di sadvantage compared w i th si ngl etons. [3][4][5][6] Tw i ns share the w omb at the same ti me and consequentl y share prenatal nutri ti on provi ded by the mother's di etary i ntake. When prepari ng for l abour, tw i ns compete for the best posi ti on.…”
Section: Introductionmentioning
confidence: 99%
“…3 A rel ati vel y smal l number of studi es has been devoted to detecti ng tw i n-si ngl eton di fferences i n cogni ti on. 4,6,15 The one study that stands out w as conducted by Record, M cKeow n and Edw ards 6 who compared an i mpressi ve number of si ngl etons, tw i ns and even a few tri pl ets. Verbal reasoni ng scores from the Bri ti sh el even-pl us exami nati on w ere gathered from 48 913 si ngl etons, 1082 tw i n pai rs and el even tri pl ets.…”
Section: Introductionmentioning
confidence: 99%
“…Parental recall of early language development has been found to correlate 0.93 with the Goldman-Fristoe Test of articulation (Johnston et al, 1984). The reliability of such self-report measures has been discussed by .…”
Section: Speech and Readingmentioning
confidence: 99%